2004
DOI: 10.1007/s00240-003-0386-2
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin B6 metabolites in idiopathic calcium stone formers: no evidence for a link to hyperoxaluria

Abstract: Vitamin B6 metabolites and their potential correlates to urinary oxalate excretion in idiopathic calcium stone formers (ICSF) compared with healthy subjects were investigated. This clinical study was performed in a population of male ICSF with (Hyperoxalurics, n=55) or without hyperoxaluria (Normooxalurics, n=57) as well as in 100 healthy male control subjects. Pyridoxal 5'-phosphate serum concentration (S-pyridoxal 5'P) and 24-h urinary excretion of 4-pyridoxic acid (U-4pyridoxic acid) were measured using HPL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 19 publications
1
9
0
Order By: Relevance
“…The chief immediate metabolic precursor of oxalate is glyoxylate, which is formed from glycolate in the peroxisomes and from hydroxyproline in the mitochondria, 7,9 so that oxalate synthesis is almost entirely dependent on the glyoxylate pathway. A key reaction in this pathway is the conversion of glyoxylate to glycine coupled with the conversion of alanine to pyruvate catalyzed by the pyridoxal phosphate (vitamin B6)‐dependent enzyme alanine: glyoxylate aminotransferase (AGT) 6,9–11 . Among the various precursors of oxalate, hydroxypyruvate, hydroxyproline, ethylene glycol, glycolate, and glyoxylate have all been shown to significantly promote oxalogenesis, 7–9,12,13 whereas glycine and ascorbate do not increase urinary oxalate excretion in rats 14,15 …”
Section: Introductionmentioning
confidence: 99%
“…The chief immediate metabolic precursor of oxalate is glyoxylate, which is formed from glycolate in the peroxisomes and from hydroxyproline in the mitochondria, 7,9 so that oxalate synthesis is almost entirely dependent on the glyoxylate pathway. A key reaction in this pathway is the conversion of glyoxylate to glycine coupled with the conversion of alanine to pyruvate catalyzed by the pyridoxal phosphate (vitamin B6)‐dependent enzyme alanine: glyoxylate aminotransferase (AGT) 6,9–11 . Among the various precursors of oxalate, hydroxypyruvate, hydroxyproline, ethylene glycol, glycolate, and glyoxylate have all been shown to significantly promote oxalogenesis, 7–9,12,13 whereas glycine and ascorbate do not increase urinary oxalate excretion in rats 14,15 …”
Section: Introductionmentioning
confidence: 99%
“…(8) More recently, a comparatively larger study analyzed the effect of a 7-day course of vitamin B6 at a dose of 300 mg/day on urinary excretion of oxalate among 55 idiopathic calcium stone formers (40 with and 15 without hyperoxaluria) and 50 healthy subjects: urine oxalate did not change substantially in any group. (9) In the HPFS and NHS cohorts, intake of total vitamin B6 was not associated with urinary oxalate excretion. (19)…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that vitamin B6 deficiency results in increased production and excretion of oxalate,(2) and supplementation of vitamin B6 has been shown to reduce urinary excretion of oxalate in some studies(3–7) but not in others. (8,9) Previous cohort studies investigating the association between intake of vitamin B6 and incident kidney stones found conflicting results, with no association among males participating in the Health Professionals Follow-up Study (HPFS)(10) and an inverse association among older females in the Nurses’ Health Study (NHS) I. (11) We sought to investigate the association between intake of vitamin B6 and incident kidney stones in the same cohorts after additional follow-up time, as well as in an additional cohort of younger females in the NHS II in which the association was not investigated before.…”
Section: Introductionmentioning
confidence: 99%
“…Epidemiologic studies suggest that supplemental vitamin B 6 intake is inversely associated with symptomatic kidney stones in women [103] but not in men [104]. Yet, the concentration of vitamin B 6 metabolites in idiopathic calcium oxalate stone formers does not appear different from nonstone formers [105]. While some data are supportive for pyridoxine supplementation along with other nutrition recommendations [50,106] or in conjunction with supplemental magnesium [107], others are not [108].…”
Section: • the Extent To Which Oxalate Biosynthesis Can Be Reduced Inmentioning
confidence: 99%